POSSIBILIDADES E LIMITES NA COOPERAÇÃO UNIVERSIDADE-EMPRESA-GOVERNO: NA ÓTICA DOS GESTORES DO CONVÊNIO UNIJUÍ-SEDAI - VITCEL, MARLISE S.; TEIXEIRA, ENISE B.; BEBER, MARLISE C. (Salão do Conhecimento, 2013)
Resumo